An Examination of Backing Effects on Ratings for Masonry Arch Bridges - Rahman, Muhammad; Fanning, P. (World Academy of Science, Engineering and Technology, 2010)
Many single or multispan arch bridges are strengthened with the addition of some kind of structural support between adjacent arches of multispan or beside the arch barrel of a single span to increase the strength of the overall structure. It was traditionally formed by either placing loose rubble masonry blocks between the arches and beside the arches or using mortar or concrete to construct a more substantial structural bond between the spans. On the other hand backing materials are present in some existing bridges. Existing arch assessment procedures generally ignore the effects of backing materials. In this paper an investigation of the effects of backing on ratings for masonry arch bridges is carried out. It is observed that increasing the overall lateral stability of the arch system through the inclusion of structural backing results in an enhanced failure load by reducing the likelihood of any tension occurring at the top of the arch.